Melanosis secondary to Addison disease: a case report - Dave, Dhaval; Mukherji, Anannya; Joshi, Manohar; Patel, Spandan; Jain, Ashwini; Pakhale, Ketan; Bhate, Archana (International Journal of Research in Medical Sciences, 2017)
Addison disease is a rare but potentially fatal disorder of the adrenal glands. Its manifestations are often confused with many common disorders, and a high index of suspicion is required for the diagnosis. In this case we observed that initially the manifestation were confused with melanosis secondary to consumption of Ayurvedic medication and pangastritis, but a high level of suspicion helped to reach the diagnosis of Addison disease.